2022
DOI: 10.1039/d2lc00280a
|View full text |Cite
|
Sign up to set email alerts
|

Label-free 1D microfluidic dipstick counting of microbial colonies and bacteriophage plaques

Abstract: Miniaturised 1D liquid colony and plaque counting method. Counting viable bacterial cells and functional bacteriophage is fundamental to microbiology underpinning research, surveillance, biopharmaceuticals and diagnostics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Nonetheless, a complete automation process should not be considered as such if it does not include the last part of the process, which is plate reading and PFU count. Fortunately, automation of these tasks is already under development, which will certainly contribute to improving phage potency assessment [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, a complete automation process should not be considered as such if it does not include the last part of the process, which is plate reading and PFU count. Fortunately, automation of these tasks is already under development, which will certainly contribute to improving phage potency assessment [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Dönmez and colleagues found that a rapid count of phage plaques in a dip-and-test format could be achieved by incorporating digital imaging with fluoropolymer microcapillaries. 271 Additionally, Ogawa and colleagues successfully differentiated between live E. coli and heat-treated E. coli within 20 min utilizing a near-field sensor array. 272…”
Section: Biosensor-based Assaysmentioning
confidence: 99%
“…Dönmez et al also utilized bacteriophages for live bacteria detection but instead of using a reporter phage, they exploited the phage's natural ability to produce lytic plaques. [75] Plaque forming units (PFU) are commonly produced in solid agar plates and require a laborious procedure and overnight incubation. In this study a microfluidic dipstick was developed for fast and simple PFU measurements, achieving a limit of detection of 250 CFU mL −1 in 4-8 h of incubation depending on the target organism.…”
Section: Metabolic Activity and Cell Culturementioning
confidence: 99%